Mesenchymal stromal cells from amniotic fluid are less prone to senescence compared to those obtained from bone marrow: An in vitro study. Issue 11 (15th June 2018) - Alessio, Nicola; Pipino, Caterina; Mandatori, Domitilla; Di Tomo, Pamela; Ferone, Angela; Marchiso, Marco; Melone, Mariarosa A.B.; Peluso, Gianfranco; Pandolfi, Assunta; Galderisi, Umberto
Abstract : Mesenchymal stromal cells (MSCs) are considered to be an excellent source in regenerative medicine. They contain several cell subtypes, including multipotent stem cells. MSCs are of particular interest as they are currently being tested using cell and gene therapies for a number of human diseases. They represent a rare population in tissues; for this reason, they require, before being transplanted, an in vitro amplification. This process may induce replicative senescence, thus affecting differentiation and proliferative capacities. Increasing evidence suggests that MSCs from fetal tissues are significantly more plastic and grow faster than MSCs from bone marrow. Here, we compare amniotic fluid mesenchymal stromal cells (AF‐MSCs) and bone marrow mesenchymal stromal cells (BM‐MSCs) in terms of cell proliferation, surface markers,  multidifferentiation potential, senescence, and DNA repair capacity. Our study shows that AF‐MSCs are less prone to senescence with respect to BM‐MSCs. Moreover, both cell models activate the same repair system after DNA damage, but AF‐MSCs are able to return to the basal condition more efficiently with respect to BM‐MSCs. Indeed, AF‐MSCs are better able to cope with genotoxic stress that may occur either during in vitro cultivation or following transplantation in patients. Our findings suggest that AF‐MSCs may represent a valid alternative to BM‐MSCs in regenerative medicine, and, of great relevance, the investigation of the mechanisms involved in DNA repair capacity of both AF‐MSCs and BM‐MSCs may pave the way to their rational use in the medical field. Abstract : We compare amniotic fluid mesenchymal stromal cells (AF‐MSCs) and bone marrow mesenchymal stromal cells (BM‐MSCs) in terms of cell proliferation, surface markers, multidifferentiation potential, senescence, and DNA repair capacity. Our findings suggest that AF‐MSCs may represent a valid alternative to BM‐MSCs in regenerative medicine.